Reformasi Digitalisasi Rantai Pasok Maritim Pasca Covid-19 - Johnson, Johnson; Jeffrey, Jeffrey; Laurence, Jenniver; Simorangkir, Enda Noviyanti (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
The maritime supply chain becomes the key factor in trade globalization especially when the pandemic hit; the maritime supply chain was interrupted and caused instability of supply and demand around the world. The pandemic crisis forced the maritime supply chain stakeholders to adopt and implement technologies to give fast and precise services that could reach remote areas. This article reviews several conducted research before and within the pandemic about the challenges and actions of digitalization transformation in the maritime supply chain. The result shows that almost all the research articles reviewed state the importance of digital transformation as the solution of the maritime supply chain interruption due to pandemic that started from the fast and on time exchanged and integrated information to automation of moving goods in the supply chain work processes. Businessmen and the government have the same conclusion that digitalization is an integral part of any solution taken.